LIFE STYLE CHANGE MASYARAKAT PERKOTAAN TERHADAP PENGGUNAAN E-COMMERCE DITINJAU DARI ASPEK MAQOSHID SYARIAH - Lita Ayudha Ningsih (Al-Iqtishad: Jurnal Ekonomi Syariah, 2022)
By the time the life style citizen has changed. The presence of various e-commerce makes it easy for people to make buying and selling transactions. However, with the existing facilities. Does it provide benefits or provide mafsadat for each individual. Because with the convenience that there is sometimes it brings redundant nature. It is difficult to distinguish between basic needs and complementary needs. Even in the science of maqhosid sharia, it has been arranged to divide the needs based on the portions. The first is the dharuriyat level) which is related to food needs, the second is the Hajjiyat level which is a secondary need, this need is after the dharuriyat level needs where if this need is not met it will not threaten survival, the last is the Tahsiniyat level, where this need is a form of need. complement that if we do not complete and fulfill these needs, our lives become less comfortable. From several aspects of the level of fulfillment of these needs, it can be analyzed how people currently complete their life needs. Follow the lifestyle or just as needed. This research was conducted with a qualitative approach, where the researcher made the object of research on office workers in the PT La Nugraha Group a broadcast media in the city of Palembang. They are part of the Lifestyle Change using E-commerce as a medium for shopping and obtaining all the necessities of life. Life style change in society is not only changing from the consumption aspect. However, it also changes people's social life. This research also illustrates how strong the influence of e-commerce has changed the habits of urban people. And, describing the level of e-commerce users that is increasing every year.